Developing guidelines for reporting healthcare research: Scientific rationale and procedures - Altman, D; Moher, D (2005)
Healthcare research is extremely important, with the clear potential to influence treatment and prevention of disease, possibly on a global scale. Yet deficiencies in how research studies are reported are both well-documented and widespread across all medical specialties, types of interventions and study designs. Although randomised trials have received the most attention in this regard, similar concerns have been expressed about reporting of other types of research including diagnostic and epidemiological studies. If a journal article describes in enough detail what was done at each stage of a study, readers will have enough information to allow them to decide on the merits of the results for themselves. From this simple idea comes the scientific rationale of developing guidelines on how to report research. We consider desirable attributes of such guidelines, emphasising the importance of being evidence-based where possible. We describe recommended processes to produce guidelines that have evolved over several years during the preparation of a sequence of reporting guidelines including CONSORT, QUOROM, STARD and STROBE.